The Challenges of Integrating Customary Water Rules Under the Formal Water Governance in Ethiopia: Towards Legal Pluralism - Degu, Temesgen Abebe (Hang Tuah Law Journal, 2025)
Customary water rules are not adequately incorporated into the Ethiopian formal water governance framework despite their vital role in ensuring sustainable and equitable utilization of scarce water resources. Using the traditional doctrinal legal research methodology, this research seeks to examine the extent of recognition given to customary water rules under the Ethiopian formal water governance regime. Drawing on the theory of institutional (in)congruence, the research makes a textual analysis of the Ethiopian formal water governance legal framework using both primary sources (national and international laws related to water governance) and secondary sources (relevant books, journal articles and online sources). The article argues that there is a limited recognition of customary water rules under the Ethiopian formal water governance system which has led to conflicts, inefficiencies, and unsustainable use of water resources. This is due to the value clash between the formal water rules built on the notion of water as a resource for commodification, and customary water rules that see water as sacred and communal part of communities sociocultural and ecological being. As a result of this value clash, customary water rules, however important sustainability tenets they might lend, are not easily amenable into the formal water governance framework without in the first place questioning its basic foundations. It is concluded that strategies such as incorporating ecosystems based approaches, recognizing and integrating traditional knowledge, and promoting participatory decision-making process can assist in bridging the gaps between the commodification and preservation values.